Aquaporin Inhibition by Gold(III) Compounds: New Insights. Issue 7 (7th May 2013) - Martins, Ana Paula; Ciancetta, Antonella; de Almeida, Andreia; Marrone, Alessandro; Re, Nazzareno; Soveral, Graça; Casini, Angela
Abstract Aquaporins (AQPs) are membrane water/glycerol channels with essential roles in biological systems, as well as being promising targets for therapy and imaging. Using a stopped‐flow method, a series of gold(III), platinum(II) and copper(II) complexes bearing nitrogen donor ligands, such as 1, 10‐phenatroline, 2, 2′‐bipyridine, 4, 4′‐dimethyl‐2, 2′‐bipyridine, 4, 4′‐diamino‐2, 2′‐bipyridine and 2, 2′;6′, 2"‐terpyridine, were evaluated in human red blood cells expressing AQP1 and AQP3, responsible for water and glycerol movement, respectively. The results showed that the gold(III) complexes selectively modulate AQP3 over AQP1. Molecular modeling and density functional theory (DFT) calculations were subsequently performed to rationalize the observations and to investigate the possible molecular mechanism through which these gold compounds act on their putative target (AQP3). In the absence of any crystallographic data, a previously reported homology model was used for this purpose. Combined, the findings of this study show that potent and selective modulation of these solute channels is possible, however further investigation is required into the selectivity of this class of agents against all AQP isoforms and their potential therapeutic uses.